2019
DOI: 10.1136/bmjopen-2018-026351
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies and associated risk factors in a Saudi population: a cohort study from pregnancy to age 2 years

Abstract: ObjectiveTo assess the three key issues for congenital anomalies (CAs) prevention and care, namely, CA prevalence, risk factor prevalence and survival, in a longitudinal cohort in Riyadh, Saudi Arabia.SettingTertiary care centre, Riyadh, Saudi Arabia.ParticipantsSaudi women enrolled during pregnancy over 3 years and their 28 646 eligible pregnancy outcomes (births, stillbirths and elective terminations of pregnancy for foetal anomalies). The nested case-control study evaluated the CA risk factor profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
23
2
1
Order By: Relevance
“…In addition, numerical chromosome abnormalities were more prominent than structural chromosome abnormalities and Down syndrome (trisomy 21) was the most common recorded anomaly. In comparison with other studies, birth prevalence of chromosome abnormalities among newborns in Medina was within international rates, however it was relevantly higher compared to national studies (25,31). Table 5 summarizes the comparison between our study and some national and international studies.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, numerical chromosome abnormalities were more prominent than structural chromosome abnormalities and Down syndrome (trisomy 21) was the most common recorded anomaly. In comparison with other studies, birth prevalence of chromosome abnormalities among newborns in Medina was within international rates, however it was relevantly higher compared to national studies (25,31). Table 5 summarizes the comparison between our study and some national and international studies.…”
Section: Discussioncontrasting
confidence: 63%
“…Folic acid combination in multivitamin supplements has been shown to reduce additional congenital anomalies. Case-control cohorts, after FA fortification, highlight the decrease in folate sensitive congenital anomaly frequencies ( Czeizel, 1996 , Jahanbin et al, 2018 , Ingrid Goh et al, 2006 , Goh and Koren, 2008 , Johnson and Little, 2008 , Lowry et al, 2019 , Morris et al, 2018 , Nishigori et al, 2019 , Kondo et al, 2019 , McDonnell et al, 2018 , Mao et al, 2017 , Liu et al, 2019 , Liu et al, 2018 , Liu et al, 2018 , Kurdi et al, 2019 , Poletta et al, 2018 , Li et al, 2013 , Godwin et al, 2008 , Canfield et al, 2005 , Canfield et al, 2009 , Ray et al, 2002 , Wilcox et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these countries, polio, malaria, and diarrhea are the three leading causes of death under five. In countries with the lowest under-5 mortality rates (such as the EURO countries), congenital anomalies are also the leading cause of death [15]. Olusanya et al reported that the 4 disorders of epilepsy, mental retardation, and visual and auditory impairments are responsible for 28.9 million (19.9%) of the healthy years lost due to disability in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that low-income countries bear a large part of the burden of infectious diseases. With regard to congenital anomalies, studies show that congenital anomalies and their risk factors are mainly seen in people with lower socioeconomic status [14,15]. For example, Clark et al in a study in Scotland, showed that the prevalence of orofacial clefts increased with the decrease in socioeconomic status [16].…”
Section: Introductionmentioning
confidence: 99%